FC 016SPARSENTAN IMPROVES GLOMERULAR BLOOD FLOW AND AUGMENTS PROTECTIVE TISSUE REMODELING IN MOUSE MODELS OF FOCAL SEGMENTAL GLOMERULOSCLEROSIS (FSGS). (29th May 2021) - Gyarmati, Georgina; Shroff, Urvi; Izuhara, Audrey; Komers, Radko; Bedard, Patricia; Peti-Peterdi, Janos
Abstract: Background and Aims: Preliminary preclinical and emerging clinical evidence indicates strong antiproteinuric actions of dual endothelin type A (ETA) and angiotensin II type 1 (AT1) receptor antagonism with sparsentan. These nephroprotective effects have been more pronounced in different experimental and clinical settings compared to current standard of care using an AT1 receptor blocker (ARB). Considering the broad spectrum of renal actions of endothelin (ET) and angiotensin II (Ang II), inhibition of both pathways using sparsentan is postulated to target multiple renal cell types via a variety of renoprotective mechanisms. The aim of this study was to determine glomerular action of sparsentan as compared to the ARB losartan (Los) by direct visualization of effects on renal hemodynamics and tissue remodeling in the intact living kidney. Method: Intravital multiphoton microscopy (MPM) of the glomerular vasculature and filtration barrier structure and function was performed in genetically engineered mice combined with traditional urinalysis and histology-based phenotyping. Glomerular hemodynamic parameters (afferent and efferent arteriole (AA and EA) diameters and single nephron glomerular filtration rate (SNGFR)) and podocyte calcium entry, as a measure of cell injury, were quantitatively visualized in the FSGS model Pod-GCaMP5/Tomato TRPC6 transgenic mice (1.5 years of age), in which TRPC6 is overexpressed together with the calcium reporter GCaMP5 in podocytes. Single cell identification and fate tracking of cells of the renin lineage (CoRL) was performed over time using a second physiologic control mouse model, Ren1d-Confetti mice that feature a multicolor CFP/GFP/YFP/FP reporter. Three groups of mice in each model received treatment with either vehicle (CTRL), the ARB losartan (Los; 10 mg/kg/day), or sparsentan (120 mg/kg/day) for 6 weeks (FSGS model) or 2 weeks (control physiology model). Results: Both Los and sparsentan treatment attenuated the acute ET + Ang II-induced elevation of podocyte calcium by ∼80%, and the development of albuminuria, and glomerulosclerosis and tissue fibrosis in the FSGS model. Notably, sparsentan prevented the ET + Ang II increases in podocyte calcium more than Los and was significantly more effective in dilating both AA and EA (Fig. 1A, B ), increasing SNGFR (Fig. 1C ), increasing capillary blood flow (2-fold; p<0.0001 vs. CTRL), and decreasing albuminuria (20%; p<0.05 vs. CTRL). Sparsentan also preserved p57+ podocyte number by 50% compared to Los (p<0.0001 vs. Los). Similarly, pretreatment with sparsentan was more effective in preventing glomerular arteriolar vasoconstriction induced by acute ET + Ang II iv injection compared to Los (p<0.05 vs. Los). Following a 2-week treatment in control healthy Ren1d-Confetti mice, sparsentan resulted in a more robust increase compared to Los in the number of Confetti+ cells, clones, and individual cells per clone in the glomeruli and AA (Fig. 1D-F ). Renal tubule segments also showed active cellular remodeling in response to sparsentan. Conclusion: Serial MPM imaging directly visualized several mechanisms underlying beneficial antiproteinuric and structural effects of sparsentan in both FSGS and in the normal mouse kidney and differences between dual ETA/AT1 receptor antagonism of sparsentan and a mono-selective ARB. The sparsentan-induced glomerular hemodynamic pattern was driven by both AA and EA dilation resulting in an increase in capillary blood flow. Compared to Los, sparsentan was more effective in attenuating ET/Ang II-induced podocyte injury and in activation of resident progenitor cells and tissue remodeling. These findings suggest multiple layers of renal protective actions by dual ETA and AT1 receptor antagonism.